On Valuation in Reportage – between Reflectiveness and Judgement - Dąbrowska, Dorota (Załącznik Kulturoznawczy, 2024)
The aim of the article is to reflect on the issue of valuating reality in reportage – a problem closely related to the issue of the creator's subjective stance and the adopted narrative strategy. The text has the character of a case study – it is focused on the analysis of two literary reportages – Powietrze tu mokre (en. Here The Air is Wet) by Małgorzata Rejmer and Zgorszenie polskie (en. Polish Scandal) by Mirosław Wlekły. The presented observations are intended to demonstrate that the typologies functioning on Polish ground and defining possible manners in which the author becomes present in a reportage text do not reflect the complexity of literary realizations of the genre.